Responding to Intraoperative Neuromonitoring Changes During Pediatric Coronal Spinal Deformity Surgery. Issue 1 (May 2019) - Lewis, Stephen J.; Wong, Ian H. Y.; Strantzas, Samuel; Holmes, Laura M.; Vreugdenhil, Ian; Bensky, Hailey; Nielsen, Christopher J.; Zeller, Reinhard; Lebel, David E.; de Kleuver, Marinus; Germscheid, Niccole; Alanay, Ahmet; et al.
Study Design: Retrospective case study on prospectively collected data. Objectives: The purpose of this explorative study was: 1) to determine if patterns of spinal cord injury could be detected through intra-operative neuromonitoring (IONM) changes in pediatric patients undergoing spinal deformity corrections, 2) to identify if perfusion based or direct trauma causes of IONM changes could be distinguished, 3) to observe the effects of the interventions performed in response to these events, and 4) to attempt to identify different treatment algorithms for the different causes of IONM alerts. Methods: Prospectively collected neuromonitoring data in pre-established forms on consecutive pediatric patients undergoing coronal spinal deformity surgery at a single center was reviewed. Real-time data was collected on IONM alerts with >50% loss in signal. Patients with alerts were divided into 2 groups: unilateral changes (direct cord trauma), and bilateral MEP changes (cord perfusion deficits). Results: A total of 97 pediatric patients involving 71 females and 26 males with a mean age of 14.9 (11-18) years were included in this study. There were 39 alerts in 27 patients (27.8% overall incidence). All bilateral changes responded to a combination of transfusion, increasing blood pressure, and rod removal. Unilateral changes as a result of direct trauma, mainly during laminotomies for osteotomies, improved with removal of the causative agent. Following corrective actions in response to the alerts, all cases were completed as planned. Signal returned to near baseline in 20/27 patients at closure, with no new neurological deficits in this series. Conclusion: A high incidence of alerts occurred in this series of cases. Dividing IONM changes into perfusion-based vs direct trauma directed treatment to the offending cause, allowing for safe corrections of the deformities. Patients did not need to recover IONM signal to baseline to have a normal neurological examination.